Internalization of Pesantren Educational Values in Community Social Life - Zulfian Zulfian; Fadhila Nur Akmalia; Anton Sudradjat (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
Islamic boarding schools are one of the oldest Islamic educational institutions in Indonesia, which play an important role in shaping religious and social values within society. This study aims to analyze the process of internalizing pesantren educational values in the social life of the community surrounding Al-Urwatul Wutsqo Islamic Boarding School in Jombang. This research employed a qualitative approach using a case study design. The research subjects consisted of pesantren leaders, teachers, students, alumni, and members of the surrounding community. Data were collected through in-depth interviews, observation, and documentation. The data were analyzed using an interactive analysis model that includes data reduction, data display, and conclusion drawing. The findings reveal that the internalization of pesantren educational values occurs through intensive social interaction between the pesantren and the community. Values such as religiosity, togetherness, social responsibility, simplicity, and mutual respect are manifested through various religious and social activities involving the community, including religious gatherings, da'wah activities, and social service programs. In addition, the exemplary leadership of the pesantren leader and the role of pesantren alumni significantly contribute to disseminating these values within society. This study contributes to the discourse of Islamic education by highlighting the strategic role of pesantren in fostering a religious and harmonious social life through the internalization of pesantren educational values.